2019
DOI: 10.1088/1755-1315/355/1/012106
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol oxidase and peroxidase activity in apple: dependency on cultivar and fruit processing

Abstract: Apples are an important source of polyphenolic and most popular fruits worldwide. Due to their phenolic content, consuming apple in a diet tend to low risk and prevention some chronic diseases. The main enzyme is responsible for quality loss, which are affecting by phenolic degradation, are polyphenol oxidase (PPO) and peroxidase (POX). PPO and POX are correlated to the rate of browning with substrate content and enzyme activity. The objective of this research was to investigate the polyphenol oxidase (PPO) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…The PPO activity was assayed at different temperatures ranging from 4 to 50°C, the enzyme showing the highest enzymatic activity at the temperature of 25°C. Our results were similar to those reported by Hutabarat and Halbwirth (2019) who assessed the presence of PPO in different apple cultivars. The majority of the PPOs presented the highest activity around the value of pH of 6.5 and temperature between 20 and 25°C.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The PPO activity was assayed at different temperatures ranging from 4 to 50°C, the enzyme showing the highest enzymatic activity at the temperature of 25°C. Our results were similar to those reported by Hutabarat and Halbwirth (2019) who assessed the presence of PPO in different apple cultivars. The majority of the PPOs presented the highest activity around the value of pH of 6.5 and temperature between 20 and 25°C.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, the lowest relative enzyme activity of 85.88% ± 1.52% and 25.82% ± 1.24% were recorded at pH 5.0 and 8.0, respectively. The PPO activity was assayed at different temperatures ranging from 4 to 50 • C, the enzyme showing the highest enzymatic activity at the temperature of 25 • C. Our results were similar to those reported by Hutabarat and Halbwirth (2019) who assessed the presence of PPO in different apple cultivars. The majority of the PPOs presented the highest activity around the value of pH of 6.5 and temperature between 20 and 25 • C. In contrast to our results, the enzyme extracted from Hemşin apple (M. communis L.) behaved optimally at pH 5.5 and at 30 • C, when catechol was used as a substrate (Aydin et al, 2015).…”
Section: Optimum Parameters For Ppo Activitysupporting
confidence: 87%
“…PPO activity, L-value, and hue angle were similar (Neri et al, 2019) Fresh-cut Bay 4152, Gala Mitslugla, Gravin Goldach, Sonnen Glanz PPO activity was not affected by color of flesh (Hutabarat & Halbwirth, 2019) Each cultivar had different PPO and POD activities Flesh Delbard Estival, Kohanz PPO activity of Kohanz was still similar to control 3 weeks after spraying with chelated and nano-chelated Zn (Rasouli & Saba, 2018) Fresh-cut Cripps Pink, Golden Delicious ΔE: Golden Delicious < Cripps Pink (Putnik et al, 2017) Fresh-cut Granny Smith, Jonagold, Pink Lady PPO activity: Granny Smith < Jonagold < Pink Lady (after HPP); no difference (after thermal) (Junjie Yi et al, 2017) POD activity: Jonagold < Granny Smith < Pink Lady (after HPP); no difference (after thermal) ΔE: Granny Smith < Pink Lady < Jonagold (after HPP); Pink Lady < Jonagold < Granny Smith (after thermal)…”
Section: Cultivars Main Findings Referencesmentioning
confidence: 84%
“…PPO and POD activities increased during 60 days of storage for all the treatments (Figure 4a,b). PPO enzymes use O 2 to catalyze the oxidation of fruits' phenolic compounds to form quinones, which ultimately leads to the formation of brown pigments [64][65][66]. PODs are instead enzymes that catalyze peroxidation, oxidation-catalytic, and hydroxylation reactions.…”
Section: Ppo and Pod Activitymentioning
confidence: 99%
“…Nonetheless, other studies reported contrasting results, as in the case of the investigation conducted by Othman [69], who reported an enhancement of PPO activity during eight days of storage for pineapple, mango, and papaya fruit. However, PPO activity is affected by many factors, such as temperature, pH of the medium, O 2 availability, amount and type of phenolic compounds in samples, and cultivars, which could be the reason for these contradictory results [66,69]. A similar trend to that seen for PPO was observed for POD enzyme, regardless of the considered batch, throughout the storage period, thus indicating that the coatings delayed the ripening and darkening reactions of apples (Figure 4b).…”
Section: Ppo and Pod Activitymentioning
confidence: 99%